The permeation of potassium ions through the lipid scrambling path of the membrane protein nhTMEM16 - Cheng, Xiaolu; Khelashvili, George; Weinstein, Harel (Frontiers in Molecular Biosciences, 2022)
The TMEM16 family of transmembrane proteins includes Ca2+-activated phospholipid scramblases (PLS) that can also function as non-selective ion channels. Extensive structural and functional studies have established that a membrane-exposed hydrophilic groove in TMEM16 PLS can serve as a translocation pathway for lipids. However, it is still unclear how the TMEM16 PLS conduct ions. A “protein-delimited pore” model suggests that ions are translocated through a narrow opening of the groove region, which is not sufficiently wide to allow lipid movement, whereas a “proteolipid pore” model envisions ions and lipids translocating through an open conformation of the groove. We investigated the dynamic path of potassium ion (K+) translocation that occurs when an open groove state of nhTMEM16 is obtained from long atomistic molecular dynamics (MD) simulations and calculated the free energy profile of the ion movement through the groove with umbrella sampling methodology. The free energy profile identifies effects of specific interactions along the K+ permeation path. The same calculations were performed to investigate ion permeation through a groove closed to lipid permeation in the nhTMEM16 L302A mutant which exhibits a stable conformation of the groove that does not permit lipid scrambling. Our results identify structural and energy parameters that enable K+ permeation and suggest that the presence of lipids in the nhTMEM16 groove observed in the simulations during scrambling or in/out diffusion, affect the efficiency of K+ permeation to various extents.